The Effect of Human Development Index (HDI), Inequality and Consumption on Poverty Levels in All Provinces in Indonesia - Abdullah; Wibowo, Muhammad Ghafur (Jurnal Ilmu Ekonomi Terapan, 2024)
This study aims to analyze the effect of human development index (HDI), income inequality, and consumption on Indonesia’s poverty rate for 2018-2022. The approach used is quantitative with statistical panel data analysis method using 3 model approaches namely CEM, FEM, and REM. The selected model is the Fixed Effect Model as a result of the Chow and Hausman tests. The results showed that HDI and inequality variables had no significant effect on the poverty rate. Meanwhile, the consumption variable has a negative and significant effect on poverty. Simultaneously, all independent variables have a significant effect on the dependent variable. This research is expected to provide input for the government in formulating poverty alleviation policies in Indonesia by focusing more on reducing public consumption. Research limitations on secondary data in aggregate so that the results are less representative for each province.